The last flower: transforming inner feelings into innovative solutions - Yeo, Jesvin Puay-Hwa (2024)
Youths in Singapore are over protected and spoiled by affluence. They have more freedom to express their thoughts and ideas, but most do not have strong opinions on issues and are not interested in their surroundings. This may hinder them from competing effectively in an increasingly globalized Singapore, even in the creative industries. They may lack the ability to generate good design ideas from their cultural background, feelings, and preferences. This article aims to find the possibility of using emotion to awaken students’ inner feelings and make them become better designers and thinkers. The design brief was inspired by an example from Paul Arden’s book, Documenting a Flower – The Last Flower. Thirty-one visual communication students participated in this research project. The learning model is based on Everaert-Desmedt’s “Process of Creating a Work of Art”, which consists of five stages: Firstness, Abduction, Deduction, Induction and Thirdness. The process of this model draws on Peirce’s (1931-1935, 5) model of scientific inquiry. Over the course of fourteen weeks, students are exposed to various recording methods, investigate alternative design solutions, learn about the history of flowers, document the drying process, and understand their feelings toward the flower. The results of this research project are promising, as the students have produced dynamic design solutions that capture the qualities and uniqueness of the flowers they selected. This research project offers maximum freedom and imagination, enabling students to make their own design decisions at every stage without the help of the instructor. Students go through a period of depression and helplessness; some of them have overcome it and become better thinkers. However, some prefer to be guided, especially regarding creative creation. This research project stimulates students’ inner feelings to a certain extent and brings higher-level learning from understanding external feelings to inner feelings, from observation and experimentation to application and innovation. The paper describes the student’s project in detail and will present the project’s process, results, and insights gained for discussion and analysis.